Evaluation Of National Immunization Day (NID) Activities Under Intensified Pulse Polio Immunization Program (IPPI) Feb 2012 in Central Gujarat, India - Rana, Manish; Gajjar, Sanju; Sharma, Rashmi; Sinha, Anish; Chudasama, Brinda; Kumar, Pradeep (National Journal of Community Medicine, 2012)
Background: It has been more than 1 year since the last case of wild polio virus occurred in the country and we are at the final phase of polio eradication. It needs to enhance/ sustain all activities of polio eradication. This study was carried out to critically evaluate the various activities undertaken and make the suggestions for improvement during the National Immunization Day (NID) of February 2012 under Intensified Pulse Polio Immunization Program (IPPI) in urban/ rural areas of Ahmedabad, Kheda and Gandhinagar districts of Central Gujarat. Methodology: External evaluators after a training cum orientation program undertook the evaluation of NID (Feb 2012) in 3 districts of Central Gujarat in identified 20 booths through assessing booth based vaccination and undertaking surveys of house to house activities and at migratory/ transit/ street sites. Results: (a) Booth based activities: Most booths were accessible and had supply of logistics (IEC materials, stationeries, vaccines, cold chain equipments, marker pens). Understaffing and last minute replacement with untrained staff and non participation of community or nongovernmental organizations (NGOs) were some of the issues. (b) House to house visits: External monitors could detect 7 missed sites with 63 unvaccinated children while the in house health supervisors could not detect any site. False P detection rates were also high for external monitors (5.3%) than in house supervisors (1.3%). (c) Migratory sites: Visit to 118 migratory sites yielded even more children as not vaccinated (16.8%). 21 transit sites showed the inadequacies of program where almost one third of children could not be checked for the vaccination. (d) Street surveys: Street surveys done after completion of NID (Based on finger markings alone) found 12.7% children as not vaccinated. Conclusions: Present communication aims to explore the problematic issues in achieving vaccination coverage, capacity building of team members and operational/ logistic aspects and provide intensive qualitative inputs.